The Influence of Principal Leadership and School Committees on Teacher Performance at SDN Cluster V in Rupat, Bengkalis Regency - Diana Diana; Suarman Suarman; Sri Kartikowati (Universitas Riau, 2022)
The interviews results with elementary school teachers in this cluster, it turns out that most teachers still use the lecture method in their learning. This raises social problems and new demands that cannot be predicted beforehand, so that education always faces problems because of the gap between what is expected and the results that can be achieved through the educational process. The research approach is associative quantitative, called quantitative. The population of this study were all teachers who were in SDN 4, 5, 6, 7, 9, and 28 Gugus V, Rupat District, Bengkalis Regency, amounting to 67 people. The sampling technique used is a saturated sample where all members of the population are used as samples. So the number of samples used in this study were 67 teachers. The results of this study: 1) There is a positive and significant influence between the variables of the Principal's Leadership on the teacher's performance at SDN Rupat. The higher the leadership given, the higher the teacher's performance. 2) There is a positive and significant influence between the variables of the School Committee on the teacher's performance at SDN Rupat. The higher the role of the school committee given, the higher the teacher's performance. 3) There is a jointly significant influence between the variables of the Principal's Leadership and the School Committee on the teacher's performance at the Rupat District Elementary School.